RISK FACTORS IN ROAD TRAFFIC ACCIDENT IN THE CITY OF PALU, INDONESIA - Arifuddin, Adhar; Napirah, Muhammad Ryman; Asfin H.S, Nur (Public Health of Indonesia, 2017)
Background: Traffic accidents are unpredictable events when they occurred. Thus, understanding the risk factors in road traffic injuries is needed.Objective: This study aims to analyze the risk factors in road traffic accidents in the city of Palu.Methods: This was an observational analytic study using case-control approach with sample of 182 respondents consisting of 91 cases and 91 controls. Purposive sampling was used based on a certain considerations made by the researchers themselves. Data were tested with Odds Ratio and analyzed by univariate and bivariate with a confidence level of 95%.Results: The results showed that the scatterbrained factor (OR = 3.180 95% CI 1.669 to 6.059), undisciplined behavior (OR = 11.990 at 95% CI 5.956 to 24.138), exceeding speed limit (OR = 4.230 95% CI 2.204 to 8.118 ), and no driving license (OR = 10.455 at 95% CI 5.274 to 20.722).Conclusion: This study concludes that the scatterbrained factor, undisciplined behavior, exceeding the speed limit, and no driving license are the risk factors for road traffic accidents in the city of Palu. It is recommended that all parties to cooperate with the good for the sake of safety and driving safety as well as prevention of road traffic accidents.